1999
DOI: 10.1029/1999ja900001
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric total electron content response to solar eclipses

Abstract: Abstract. On October 24, 1995, and March 9, 1997, two solar eclipse events occur. It is therefore of interest to investigate how the ionosphere responded to the eclipses. Five global positioning system (GPS) ground-based receivers are specifically designed to observe large-scale ionospheric variations over the geomagnetic equatorial, equatorial anomaly crest, and midlatitude regions. Two-dimensional images of ionospheric total electron content (TEC) during the two eclipse periods are constructed. The deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 14 publications
8
89
1
Order By: Relevance
“…5). The observed TEC depletion is higher than those reported earlier for the 1999 and 2005 eclipses by Jakowski et al ( , 2008 and also others (Tsai & Liu 1999;Rashid et al 2006). Jakowski et al (2008) found TEC reduction of up to several TEC units and the total plasma depletion of about 40% during the eclipse on August 11, 1999 and about 30% during the eclipse on October 3, 2005.…”
Section: Tec Measurementscontrasting
confidence: 49%
See 3 more Smart Citations
“…5). The observed TEC depletion is higher than those reported earlier for the 1999 and 2005 eclipses by Jakowski et al ( , 2008 and also others (Tsai & Liu 1999;Rashid et al 2006). Jakowski et al (2008) found TEC reduction of up to several TEC units and the total plasma depletion of about 40% during the eclipse on August 11, 1999 and about 30% during the eclipse on October 3, 2005.…”
Section: Tec Measurementscontrasting
confidence: 49%
“…This explanation is only valid if the background ionosphere behaves regularly, i.e., external forces of non-eclipse origin can be ignored. In other cases, the delay times may range up to 120 min as reported by Tsai & Liu (1999) when studying the solar eclipses on October 24, 1995 and March 9, 1997 at low latitudes. Furthermore, Afraimovich et al (2002) reported very short response times of only a few minutes.…”
Section: Vertical Sounding Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Ionospheric eclipse observations make a worthwhile contribution to study transient properties due to decreasing in the ionizing radiation from the Sun. Scientists have been using the total electron content (TEC) derived from ground-based receivers of the global positioning system (GPS) to monitor the source-response relation between the ambient rates of production, chemical loss, and motion of ionization (see papers listed in Afraimovich et al, 1998;Tsai and Liu, 1999;Jakowski et al, 2002;Le et al, 2009).…”
Section: Introductionmentioning
confidence: 99%